Purification of clove oil via middle vessel batch distillation - Nurul Shamsinar, Shahirin (2008)
Batch distillation process is becoming increasingly important because of its flexibility. However, regular batch distillation required high energy consumption and high residence time in the column. Middle Vessel Batch Distillation is one of the alternative configurations to overcome these problems. In this study, Middle Vessel Batch Distillation is used to purify crude clove oil. The scopes of this study are based on the effects of vessel holdup and operating time of distillation process. The objectives are to obtain the separation performance of clove oil by using middle vessel batch distillation column and to find out the effects of time and the middle vessel holdups to the composition of Eugenol in clove oil. The samples of clove oil after the process are analyzed by Gas Chromatography. The performance separation of the Middle Vessel Batch Distillation column is fully understood. It is proven that by varying vessel holdup and operating time, the separation performances are improved.